Oral Tori in Chronic Hemodialysis Patients - Chao, Pei-Jung (Biomed Res Int, 2015)
Background. This study investigated the epidemiology of torus palatinus (TP) and torus mandibularis (TM) in hemodialysis patients and analyzed the influences of hyperparathyroidism on the formation of oral tori. Method. During 2013, 119 hemodialysis patients were recruited for dental examinations for this study. Results. The prevalence of oral tori in our sample group was high at 33.6% (40 of 119). The most common location of tori was TP (70.0%), followed by TM (20.0%), and then both TP and TM (10.0%). Of the 40 tori cases, most (67.5%) were <2 cm in size; moreover, the majority (52.5%) were flat in shape. In symmetry, most (70.0%) occurred in the midline, followed by bilateral sides (20.0%). Notably, the levels of intact parathyroid hormone did not differ in patients with or without tori (P = 0.611). Furthermore, patients with tori did not differ from patients without tori in inflammatory variables such as log high-sensitivity C-reactive protein (P = 1.000) or nutritional variables such as albumin (P = 0.247). Finally, there were no differences between patients with and without tori in adequacy of dialysis (P = 0.577). Conclusions. Neither hyperparathyroidism nor inflammation malnutrition syndrome was found to contribute to the formation of oral tori in chronic hemodialysis patients. Further studies are warranted.